Weight of an Hourglass – Theory and Experiment in Quantitative Comparison - Sack, Achim; Pöschel, Thorsten (American Journal of Physics, 2017)
A flowing hourglass changes its weight in the course of time because of the accelerated motion of its center of mass. While this insight is not new, it is frequently said that the effect is tiny and hardly measurable. Here we present a simple experiment which allows to monitor the weight as a function of time revealing different stages, in quantitative agreement with theory.